Synthesis of some Acetylenic Amino Derivatives from Salicylic Acid - Zenab F. Saeed (College of Education for Pure Sciences, 2010)
ABSTRACT New derivatives of acetylenic amines containing salicylate group have been synthesized through Mannich reaction which involved reaction of propargyl salicylate with paraformaldehyde and secondary amines.The structural formula of the synthesized compounds have been investigated by physical and spectroscopic methods.